SOP: emergency workup in patients with suspected acute bacterial meningitis - Susanne Dyckhoff-Shen; Uwe Koedel; Hans-Walter Pfister; Matthias Klein (Neurological Research and Practice, 2021)
Abstract Introduction Despite antibiotic therapy, adjunctive treatment with dexamethasone, and care on modern intensive care units, bacterial meningitis remains a life-threatening disease with a high mortality and morbidity. One of most critical factors that influences outcome is a targeted quick but profound workup and early initiation of therapy in the Emergency Department. This standardized operating procedure was designed to guide physicians through the workup of patients with suspected acute bacterial meningitis. First steps In patients with suspected community-acquired bacterial meningitis, the first steps aim at establishing a diagnosis and at starting empiric therapy without delay. Therefore, physicians need to seek for an early lumbar puncture that can be done safely without prior imaging if clinical signs that point at contraindications of a lumbar puncture are absent. Immediately after lumbar puncture, empiric therapy with ceftriaxone, ampicillin and dexamethasone should be started. In regions with a critical resistance rate of pneumococci against third generation cephalosporines, vancomycin or rifampicin need to be added. Comments Clinical signs that are associated with intracranial conditions that are a contraindication for a lumbar puncture are severely decreased consciousness, new onset focal neurological signs, and epileptic seizures. If any of these clinical signs are present, cerebral imaging is recommended before lumbar puncture. Whenever lumbar puncture is delayed, empiric therapy needs to be begun before cerebrospinal fluid is obtained. Conclusion Suspected acute bacterial meningitis is an emergency and requires attention with high priority in the emergency department to ensure a quick workup and early start of therapy.